Gene expression and regulation in the yeast metabolic cycle - Feltham, J (2018)
Biological oscillations such as the circadian rhythm are central to physiology of organisms ranging from humans to bacteria. By coupling cellular processes to a periodic oscillator or "clock", cells can pro-actively coordinate their behaviour with periodic changes in their environment such as cycles of the Earth and the Moon. Defects in these processes can lead to diseases ranging from diabetes to cancer and improving these processes has the potential to enhance yields from crops and bioreactors. As such, a thorough understanding of the mechanisms underlying biological rhythms is critical for medical, agricultural and industrial applications. The yeast metabolic cycle is a model ultradian rhythm that can be induced in prototrophic S. cerevisiae cells under nutrient-limiting conditions. However, very little is known about either the role of post-transcriptional gene-regulation in maintenance of metabolic cycling or the extent to which protein levels cycle. In order to better understand these processes, this study examines the effects of disruption of RNA degradation pathways on transcript cycling and uses polysome profiling, RiboSeq & proteomics to assess the impact of cycling transcripts on the proteome of the yeast metabolic cycle. We find that low rates of protein turnover effectively suppress transcriptional cycling at the protein level and argue that the role of cycling mRNA levels in the yeast metabolic cycle is to control steady-state rather than dynamic protein levels, coupling gene expression to growth rate and nutrient availability.